Sedad Hakki Eldem. An aristocratic architect and more - ACCIAI, Serena (Studi e saggi, 2018)
The volume is dedicated to the theoretical and constructed work of Sedad Hakki Eldem. As part of a line of research on the Mediterranean and its ability to combine the settlement principles, the book focuses on the ability of the ancient world to work out a project, applied to the story of Sedad Hakki Eldem, a key person of 20th Century Turkish architecture and the one who most of all tried with his work to give Turkish modern architecture a vernacular character. The book studies the work of the Turkish architect through the key themes of the construction of the city, such as the analysis of monuments and houses, and also deals with the theme of travelling, Eldem's legacy to the city of Istanbul and his relationship with the Turkish-Ottoman house read as a primary reference for modern Turkish architecture.